2013
DOI: 10.1590/0037-8682-1060-2013
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to amphotericin B of Candida spp. strains isolated in Ceará, Northeastern Brazil

Abstract: Introduction: Amphotericin B (AMB) is an antifungal agent used extensively in clinical medicine, yet resistance remains low. This study aims to evaluate the susceptibility of Candida spp. against AMB. Methods: For broth microdilution susceptibility testing, 77 strains of Candida spp. were selected (32 C. albicans, 33 C. tropicalis, and 12 C. parapsilosis). The strains were considered susceptible when they exhibited MIC≤1.0µg/ml. Results: None of the strains showed an MIC greater than 0.25µg/ml. Conclusions: Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Three papers were placed on the agar. The minimum inhibitory concentration (MIC) of AMB for C. albicans is 0.2-1.0 µg/mL, 16 and thus 2.5, 5, 10, 20, and 40 µL of AMB-NPs, at 10.6 µg/mL (equivalent to 1.0 µg/mL AMB), and free AMB, at 1.0 µg/mL, were separately dropped onto the filter paper, followed by incubation for 4 hours at room temperature. Then, the plates were incubated at 28°C for 9 days, and digital photographs were taken.…”
Section: Antifungal Activity In Vitromentioning
confidence: 99%
“…Three papers were placed on the agar. The minimum inhibitory concentration (MIC) of AMB for C. albicans is 0.2-1.0 µg/mL, 16 and thus 2.5, 5, 10, 20, and 40 µL of AMB-NPs, at 10.6 µg/mL (equivalent to 1.0 µg/mL AMB), and free AMB, at 1.0 µg/mL, were separately dropped onto the filter paper, followed by incubation for 4 hours at room temperature. Then, the plates were incubated at 28°C for 9 days, and digital photographs were taken.…”
Section: Antifungal Activity In Vitromentioning
confidence: 99%
“…The present study also agrees with that of [22] who reported that Amphotericin B was the most effective drug to which all isolates of Candida species except C. krusei were 100% sensitive. Other reports of very high susceptibility of Candida species to Amphotericin B have been documented [17,31,24]. Owing to its high toxicity (especially nephrotoxicity) and low bioavailability (when administered orally), Amphotericin B is not regularly prescribed or used extensively.…”
Section: In Vitro Susceptibility Profile Of the Candida Species To Nymentioning
confidence: 99%
“…showed cross resistance between Azoles (20) and Terbinafine too (21). The total percentage of cross resistance was 62% (13/21) and the maximum was seen in C. albicans, C. glabrata, C.krusei and C. guilliermondii (Table 3).…”
Section: Cross Resistance Pattern Amongmentioning
confidence: 99%